Emily Bronte's Wuthering Heights - Selway, Mary.; Devlin, Anne.; Kosminsky, Peter; Binoche, Juliette, 1964-; Fiennes, Ralph; McTeer, Janet; Ward, Sophie, 1964-; Shepherd, Simon; Northam, Jeremy, 1961-; Riddington, Jason; Ward, Simon, 1941-2012.; Sullivan, Dick.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2003)
An adaptation of Emily Bronte's classic novel about two mismatched lovers and the terrible vengeance one takes on the people he blames for tearing them apart.
Title from container.
Originally released as a motion picture in 1992.
Based on the novel by Emily Bronte.
Director of photography, Mike Southon ; film editor, Tony Lawson ; music, Ryuichi Sakamoto ; costume designer, James Acheson ; production designer, Brian Morris.
Juliette Binoche, Ralph Fiennes, Janet McTeer, Sophie Ward, Simon Shepherd, Jeremy Northam, Jason Riddington, Simon Ward, Dick Sullivan.
MPAA rating: PG.
Keywords: Love -- Drama; Man-woman relationships -- England -- Yorkshire -- Drama; Video recordings for hard of hearing people; England -- Social life and customs -- 19th century -- Drama; Feature films; Video recordings for hard of hearing people